MEMASYARAKATKAN PANCASILA MELALUI ETOS KERJA, INTEGRITAS, DAN KEBIJAKAN ORGANISASI YANG BERKEADILAN - Liswandi, Liswandi; Mapuasari, Supeni Anggraeni (JURNAL ABDIMAS PLJ, 2023)
Understanding Pancasila and applying it to everyday life can make life more calm and peaceful in society. Pancasila covers various aspects of life, both interactions with fellow humans and with God. In the current conditions, the issue of integrity can reduce the quality of Indonesian human resources. Therefore, the introduction of Pancasila values to the community can be used as an option to remind the values and norms of life that are in harmony with the community. Pancasila value introduction activity is carried out online in the form of webinars and discussions. Participated by hundreds of participants consisting of students from various campuses, the Pancasila dialogue can be one of the concrete steps to strengthen the integrity of today's young generation. Keywords: Pancasila Values, Integrity, Work Ethic